Stromal Collagen Content in Breast Tumors Correlates With In Vivo Diffusion‐Weighted Imaging: A Comparison of Multi b‐Value DWI With Histologic Specimen From Benign and Malignant Breast Lesions. Issue 6 (13th December 2019) - Egnell, Liv; Vidić, Igor; Jerome, Neil P.; Bofin, Anna M.; Bathen, Tone F.; Goa, Pål Erik
Abstract : Background: Increased deposition and reorientation of stromal collagen fibers are associated with breast cancer progression and invasiveness. Diffusion‐weighted imaging (DWI) may be sensitive to the collagen fiber organization in the stroma and could provide important biomarkers for breast cancer characterization. Purpose: To understand how collagen fibers influence water diffusion in vivo and evaluate the relationship between collagen content and the apparent diffusion coefficient (ADC) and the signal fractions of the biexponential model using a high b ‐value scheme. Study Type: Prospective. Subjects/Specimens: Forty‐five patients with benign ( n = 8), malignant ( n = 36), and ductal carcinoma in situ ( n = 1) breast tumors. Lesions and normal fibroglandular tissue ( n = 9) were analyzed using sections of formalin‐fixed, paraffin‐embedded tissue stained with hematoxylin, erythrosine, and saffron. Field Strength/Sequence: MRI (3T) protocols: Protocol I: Twice‐refocused spin‐echo echo‐planar imaging with: echo time (TE) 85 msec; repetition time (TR) 9300/11600 msec; matrix 90 × 90 × 60; voxel size 2 × 2 × 2.5 mm 3 ; b ‐values: 0 and 700 s/mm 2 . Protocol II: Stejskal–Tanner spin‐echo echo‐planar imaging with: TE: 88 msec; TR: 10600/11800 msec, matrix 90 × 90 × 60; voxel size 2 × 2 × 2.5 mm 3 ; b ‐values [0, 200, 600, 1200, 1800, 2400, 3000] s/mm 2 . Assessment: Area fractions of cellular and collagen content in histologic sections were quantified using whole‐slide image analysis and compared with the corresponding DWI parameters. Statistical Tests: Correlations were assessed using Pearson's r . Univariate analysis of group median values was done using the Mann–Whitney U ‐test. Results: Collagen content correlated with the fast signal fraction ( r = 0.67, P  < 0.001) and ADC ( r = 0.58, P  < 0.001) and was lower ( P  < 0.05) in malignant lesions than benign and normal tissues. Cellular content correlated inversely with the fast signal fraction ( r = –0.67, P  < 0.001) and ADC ( r = –0.61, P  < 0.001) and was different ( P  < 0.05) between malignant, benign, and normal tissues. Data Conclusion: Our findings suggest stromal collagen content increases diffusivity observed by MRI and is associated with higher ADC and fast signal fraction of the biexponential model. Level of Evidence: 3 Technical Efficacy Stage: 3 J. Magn. Reson. Imaging 2020;51:1868–1878.